Translation And Communication Model Of Chinese Literature: A Case Study Of Cultural Communication Of English Translation Of Li Bai’S Selected Poems - Chang, Hongjing (2024)
Translation acts as a vital bridge in intercultural communication. However, significant inequalities persist in the international communication of translated literature, including english translations of chinese literature. At present, most studies focus on isolated elements of translation and communication (tc) within chinese literature, leaving the translation and communication model for chinese literature—especially classical chinese poetry—yet to be fully developed. This study aims to investigate the translation and communication model of chinese literature in the west taking li bai’s poetry as an example. Quantitative analysis was applied to data obtained from the translation and communication questionnaire, the reader response questionnaire on translations of classical chinese poetry, and the worldcat database, while qualitative analysis was conducted on data from interviews and english translations of li bai’s poetry. Additionally, both quantitative and qualitative analyses were applied to data from the jastor database, amazon, and goodreads websites.